Beberapa Variabel yang Mempengaruhi Pertumbuhan Modal Sendiri - Edwin Agus Buniarto (JURNAL AKUNTANSI, EKONOMI dan MANAJEMEN BISNIS, 2016)
This research analyzes several variables affect the growth of their own capital yng some cooperatives around Malang and Pasuruan in East Java province. These variables, among others, return on assets (ROA), debt to equity ratio (DER) pertumbuhn reserve fund (Retention ratio), interest and taxes. The sample was the annual financial statements of six cooperative during the last 5 years (30 samples) were analyzed by linear regression and assisted software SPSS, the obtained results of the analysis that the ROA, DER, retention ratio and interest payments have a significant effect on the growth of its own capital, whereas tax payments not significant effect on the growth of own capital of cooperatives in Malang and Pasuruan, East Java.